Selectived and Reshaped Early Dominant Microbial Community in the Cecum With Similar Proportions and Better Homogenization and Species Diversity Due to Organic Acids as AGP Alternatives Mediate Their Effects on Broilers Growth - Hu, Yan; Wang, Laidi; Shao, Dan; Wang, Qiang; Wu, Yuanyuan; Han, Yanming; Shi, Shourong (Frontiers in Microbiology, 2020)
Understanding the differences in microbial communities shaped by different food selective forces, especially during early posthatch period, is critical to gain insight into the effects of organic acids (OAs) as antibiotic growth promoter (AGP) alternatives on growth performance in broilers. As a model system, commercial diet-administered OAs (DOA) and water-administered OAs (WOA) were used separately or in combination as Virginiamycin alternatives for broiler feeding during 2 growth phases: 1 to 21 days and 22 to 42 days. Among these three OA-treated groups, the DOA group was most similar to the AGP group in the composition and the proportion of these dominant bacterial communities at the level of phylum, family, and genus in cecal digesta of broilers. Subtherapeutic Virginiamycin decreased the richness, homogenization and species diversity of gut microbiota, especially in the early growth stage from days 1 to 21. Among these three OA supplementation schemes, it was clear that DOA supplementation was more likely to increase or maintain the richness, homogenization, species diversity and predicted gene functions of cecal microbiota in treated broilers than either no supplementation or AGP supplementation during two experimental stages. The interference of DOA treatment with early colonization of probiotics and pathogens in broiler cecum was the most similar to AGP treatment, and OAs did not cause the occurrence of Virginiamycin-resistant strains of Enterococcus at the end of this trial. In terms of the predicted gene functions of the microbiota, AGP and DOA treatments provided a similar selective force for microbial metabolism functions in the cecum of broiler chickens, especially in the early growth stage. Noticeably, the relative abundance of some microbiome that was modified by Virginiamycin or DOA supplementation was significantly correlated with body weight gain and KEGG pathway analysis-annotated gene functions such as replication and repair, translation, nucleotide metabolism and so on. These results suggest that the formation of intestinal microecology under such early selection forces may be the root cause of growth promotion in food animals. With the comprehensive analysis of these results and practical application, DOA supplementation, after optimization of the amount of addition, would be a suitable alternative to subtherapeutic Virginiamycin.